Pharmacology of Hormone Replacement Therapy in Menopause - Voican, Adela; Francou, Bruno; Novac, Liliana; Chabbert-Buffet, Nathalie; Canonico, Marianne; Meduri, Geri; Lombes, Marc; Scarabin, Pierre-Yves; Young, Jacques; Guiochon-Mantel, Anne; Bouligand, Jérôme (IntechOpen, 2012)
None